Economic Analysis of Utilization of Corn Stover for Bioenergy Production: Towards Diversifying Income Opportunities for Small Farmers - Alegbeleye, Ibukun D.; Illukpitiya, Prabodh (Journal of Technology Innovations in Renewable Energy, 2019)
Bioenergy production from plant wastes such as corn stover has the potential to improve energy security and mitigate climate change in the United States. However, there is a limited understanding of its utilization and economic potentials for bioenergy production. The overall objective of the study was to estimate the economic profitability of utilizing corn stover for different ventures after harvesting corn, which includes: 1) corn stover production, 2) ethanol production, and 3) electricity generation through on-farm gasifiers. The data for this study was based on secondary data from various sources. The benefit-cost model was applied for the analysis. Investment evaluation criteria include annualized net return from corn stover, ethanol, and electricity generation. Results show that under current conversion rate, the net return from marketing corn stover ranges from 80.61/kg to 394.11/kg, while the net return from ethanol production ranges from -104.91/ha to 848.96/ha of corn stover under varying price and yield scenarios. Also, under the government subsidy scheme that covers 25% of equipment costs, there is an investment opportunity for on-farm gasifier with an NPV of 4,329.29. The findings of the study show the potential for using corn stover for bioenergy production since it showed a positive net return. Also, the production of ethanol from corn stover is not only economically feasible but also socially acceptable since it does not compete with food production, and serves as a means of income diversification for corn farmers. Keywords: Corn stover, plant waste, biofuel, ethanol, benefit-cost, gasifier.